A Study on The Characteristics of Physical and Mental Development of Students in The Primary Education Stage and Countermeasures of Wushu Teaching - Song, Yazhou; Shapie, Mohamad Nizam Mohamed (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Studi Purpose As the future of the motherland and the hope of the nation, primary school students shoulder the historical mission and important task of realizing the great rejuvenation of the Chinese nation. The current stage of primary education has become an important position for the popularization and promotion of Chinese martial arts. At present, physical education teachers in primary schools do not know enough about the characteristics of students' physical and mental development, which leads to the inability of physical education teachers to carry out martial arts teaching scientifically and effectively. Therefore, this study mainly adopts the literature method to study the characteristics of physical function development and psychological development of primary school students, and reveals the influence of different physical function and psychological development characteristics on wushu teaching in primary school. Research shows that primary school students are at a critical stage of physiological and psychological development, and the development of bone, muscle, respiratory, cardiovascular and nervous systems is not mature. Teachers should consider these physiological characteristics when designing Wushu courses to avoid excessive load and ensure that students train in a safe environment. At the same time, the psychological development of primary school students is also in a stage of rapid change, with an intense curiosity and imitation ability. However, the attention and willpower are relatively weak. Therefore, the teaching method should focus on stimulating students' interest, cultivating good emotional expression and teamwork ability, and promoting the development of their memory, thinking and comprehensive quality through effective teaching design, so as to provide scientific and effective countermeasures for primary school physical education teachers to carry out martial arts teaching, so as to better popularize and promote Chinese martial arts in the primary education stage.